First flavor-tagged determination of bounds on mixing-induced CP violation in Bs0→J/ψ decays - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
This Letter describes the first determination of bounds on the CP-violation parameter 2βs using Bs0 decays in which the flavor of the bottom meson at production is identified. The result is based on approximately 2000 Bs0→J/ψ decays reconstructed in a 1.35fb-1 data sample collected with the CDF II detector using pp̄ collisions produced at the Fermilab Tevatron. We report confidence regions in the two-dimensional space of 2βs and the decay-width difference ΔΓ. Assuming the standard model predictions of 2βs and ΔΓ, the probability of a deviation as large as the level of the observed data is 15%, corresponding to 1.5 Gaussian standard deviations. © 2008 The American Physical Society.